Research priority setting in Barrett's oesophagus and gastro-oesophageal reflux disease. (November 2017) - Britton, James; Gadeke, Lisa; Lovat, Laurence; Hamdy, Shaheen; Hawkey, Chris; McLaughlin, John; Ang, Yeng
Summary: The incidence of gastro-oesophageal reflux disease and Barrett's oesophagus is increasing. Barrett's oesophagus is the main precursor to oesophageal adenocarcinoma, which has a poor prognosis. In view of the vast potential burden of these diseases on patients and health-care resources, there is a real need to define and focus research efforts. This priority setting exercise aimed to produce a list of the top ten uncertainties in the field that reflect the priorities of patients and health-care providers. We adopted the robust and transparent methodologies previously outlined by the James Lind Alliance. This qualitative approach firstly involves an ideas gathering survey that, once distilled, generates a longlist of research uncertainties. These uncertainties are then prioritised via an interim ranking survey and a final workshop to achieve consensus agreement. The initial 629 uncertainties, generated from a survey of 170 individual respondents (47% professional, 53% non-professional) and one workshop, were narrowed down to the final top ten uncertainties of priority for future research. These priorities covered a range of issues, including a need for improved patient risk stratification, alternative diagnostic and surveillance tests, efficacy of a dedicated service for Barrett's oesophagus, cost-effectiveness and appropriateness of current surveillance, advances in development of non-drug treatments for gastro-oesophageal reflux disease, safety of long-term drug treatment, and questions regarding the durability and role of different endoscopic therapies for dysplastic Barrett's oesophagus. This is the first patient-centred assessment of priorities for researchers in this chronic disease setting. We hope that recognition and dissemination of these results will shape the future direction of research and translate into meaningful gains for patients.